Future Aspects in Human Cryopreservation - Safaa Al-Hasani; Khaled Zohni (Tehran University of Medical Sciences, 2008)
The capability to preserve human oocytes, blastocysts, ovarian tissue and spermatozoa is an important tool in human assisted reproductive techniques. This preservation allows patients undergoing chemotherapy or radiotherapy to preserve their fertility, and helps to attain all benefits from the costly ovarian superovulation therapies prior to ART. The primary goal in establishing an appropriate freezing protocol is to do as little damage as possible while exposing specimens to nonphysiologic ultra low temperatures. Nowadays two techniques are used in cryopreservation: the slow cooling method and the more recent rapid procedure  of vitrification. Vitrification is simple, requires no expensive programmable freezing equipment, efficient and cost effective way to improve cumulative pregnancy rates per cycle. Oocytes, blastocysts, ovarian tissue and spermatozoa could be suitable for vitrification and thus cryopreservation. Vitrification proved to be the future of cryopreservation and important progresses are achieved everyday in this active domain in a trial to set the optimal protocol for cryopreservation of different types of gametes, embryos and tissue.